Land of fertility III the southeast Mediterranean from the Bronze Age to the Muslim conquest - Miszk, Łukasz; Wacławik, Maciej (Cambridge Scholars Publishing, 2019)
"The papers in this volume are based on presentations given at the third and fourth international conferences of the ""Land of Fertility: The Southeast Mediterranean from the Bronze Age to the Muslim Conquest"" series. The first of them 'The Migration of People, Goods and Ideas in Ancient Times', was held at the Institute of Archaeology, Jagiellonian University in Kraków, on June 10-11 2016 ... The fourth conference, entitled 'Egyptian Perspective: Ancient civilisations in relation to The Two Lands', was held on June 9-10, 2017."--Preface